Integrated Comparative Genomic Analysis and Phenotypic Profiling of Pseudomonas aeruginosa Isolates From Crude Oil - Xu, Anming; Wang, Di; Ding, Yichen; Zheng, Yaqian; Wang, Bo; Wei, Qing; Wang, Shiwei; Yang, Liang; Ma, Luyan Z. (Frontiers in Microbiology, 2020)
Pseudomonas aeruginosa is an environmental microorganism that can thrive in diverse ecological niches including plants, animals, water, soil, and crude oil. It also one of the microorganism widely used in tertiary recovery of crude oil and bioremediation. However, the genomic information regarding the mechanisms of survival and adapation of this bacterium in crude oil is still limited. In this study, three Pseudomonads strains (named as IMP66, IMP67 and IMP68) isolated from crude oil were taken for whole-genome sequencing by using a hybridized PacBio and Illumina approach. The phylogeny analysis showed that the three strains were all P. aeruginosa species and clustered in clade 1, the group with PAO1 as a representitive. Subsequent comparative genomic analysis revealed a high degree of individual genomic plasticity, with a probable alkane degradation genomic island, one type I-F CRISPR-Cas system and several prophages integrated into their genomes. Nine genes encoding alkane hydroxylases (AHs) homologues were found in each strain, which might enable these strains to degrade alkane in crude oil. P. aeruginosa can produce rhamnolipids (RLs) biosurfactant to emulsify oil, which enables their survival in crude oil enviroments. Our previous report showed that IMP67 and IMP68 were high RLs producers, while IMP66 produced little RLs. Genomic analysis suggested that their RLs yield was not likely due to differences at genetic level. We then further analyzed of quorum sensing (QS) signal molecules that regulate RLs synthesis. IMP67 and IMP68 produced more N-acyl-homoserine lactones (AHLs) signal molecules than that of PAO1 and IMP66, which explained their high RLs yield. This study provides evidences for adaptation of P. aeruginosa in crude oil and proposes the potential application of IMP67 and IMP68 in microbial-enhanced oil recovery and bioremediation.